2017
DOI: 10.1177/1356336x17743048
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and measurement of playtime physical activity in English primary school children: The influence of socioeconomic status

Abstract: Children in areas of low socioeconomic status might face barriers to physical activity during school playtime in comparison to their high socioeconomic status counterparts. However, limited research within the area currently prevents evidence-based interventions to be targeted appropriately. This exploratory study aimed to assess and compare playtime physical activity levels and perceptions of physical activity in primary school children from two schools of different socioeconomic status. Fifty-three children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…The qualitative data explained that participant's perceptions of PA showed some similarities between schools A and B. It was concluded that participants have different reasons for taking part in PA, therefore, their perception to use the playground was given as an idea to improve PA (McWhannell, Triggs and Moss, 2017). Also, (McPherson et al, 2018) supported the claims that PA has a significant effect on the academic performance of students at all levels of education.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The qualitative data explained that participant's perceptions of PA showed some similarities between schools A and B. It was concluded that participants have different reasons for taking part in PA, therefore, their perception to use the playground was given as an idea to improve PA (McWhannell, Triggs and Moss, 2017). Also, (McPherson et al, 2018) supported the claims that PA has a significant effect on the academic performance of students at all levels of education.…”
Section: Introductionmentioning
confidence: 75%
“…The participants from School B remarked that they engage in PA simply to become healthy and stronger than those from participants from School A. The study revealed participation in sports activity makes the students have more fun (McWhannell, Triggs and Moss, 2017). The qualitative data explained that participant's perceptions of PA showed some similarities between schools A and B.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This study found that, on average, boys were more active than girls, and numerous studies have discussed the differences between boys’ and girls’ PA [ 41 , 42 ]. This study found a unique time-segmented gender gap, with a six-minute difference in MVPA in favour of boys during curriculum time and recess time, and a sixteen-minute difference during out-of-school time.…”
Section: Discussionmentioning
confidence: 99%
“…parents, relatives, good friends) can have a marked impact on children's intrinsic motivation [10,13]. Previous studies have reported that if children understand that sports are bene cial for health, they are more willing to participate and that children from high and medium socioeconomic backgrounds recognise more physical activity bene ts than children from low socioeconomic backgrounds [14][15][16]. Generally, children from low socioeconomic backgrounds also experience less parental support and encouragement for physical activity than children from middle and high socioeconomic homes [15].…”
Section: Introductionmentioning
confidence: 99%